2017
DOI: 10.12659/msm.903324
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Experience of Primary Cardiac Tumor: Single-Institution 23-Year Report

Abstract: Background:Primary cardiac tumors are rare but have favorable surgical prognosis. Previous studies have been small series studies with limited surgical approaches. To date, few studies have examined the clinical features associated with different surgical procedures. Material/Methods:In a search of the cardiovascular surgery database of our institution, we retrospectively identified 225 patients who had cardiac tumor resection from January 1993 to May 2016. The patients' clinical characteristics and operation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 18 publications
(23 reference statements)
1
14
0
2
Order By: Relevance
“…Most commonly noted post-operative complications with cardiac lipoma excision include arrhythmias, pneumonia and bleeding. In addition, cardiac lipoma may recur[ 16 , 17 ]. With our patient’s unusual tumor features and location in addition to, several comorbidities, surgical resection was proscribed and symptom management with antiarrhythmics showed only limited success.…”
Section: Discussionmentioning
confidence: 99%
“…Most commonly noted post-operative complications with cardiac lipoma excision include arrhythmias, pneumonia and bleeding. In addition, cardiac lipoma may recur[ 16 , 17 ]. With our patient’s unusual tumor features and location in addition to, several comorbidities, surgical resection was proscribed and symptom management with antiarrhythmics showed only limited success.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of primary cardiac tumors varies between 0.001 and 0.03%, and 0.3-0.85% of all open-heart surgeries are for cardiac tumor resections [4,5]. Twenty-five percent of primary cardiac tumors are malignant, with sarcoma accounting for a majority of the reported cases [6]. Most of the primary cardiac tumors reported in our series of 82 patients were benign (91%), and atrial myxoma was the most common type (87%).…”
Section: Discussionmentioning
confidence: 99%
“…For malignant cardiac tumors, however, the literature reports a dismal prognosis [8]. Survival rates vary from 7 months to a maximum of 2 years from diagnosis [6,8]. On long-term follow-up, the majority of patients die of distant metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al, 26 reported a single-institution, 23-year report of the resection of primary cardiac tumours in 228 patients. Within the cohort, there were 156 traditional open operations, 60 robotic neoplasm resections, and 12 procedures performed through mini-thoracotomy.…”
Section: Other Proceduresmentioning
confidence: 99%